Intracranial Stenting: Is It Still an Option for Treatment of Patients With Intracranial Atherosclerosis? - Abualhasan, Ahmed; Abd-Allah, Foad; Pero, Guglielmo; Sobh, Khaled; Mansour, Ossama; El-Serafy, Omar; Boccardi, Edoardo (Frontiers in Neurology, 2019)
Intracranial atherosclerotic disease (ICAD) is considered a major cause of recurrent cerebrovascular events. ICAD continues to be a disease without an effective method of reducing the risk of recurrent stroke and death, even with aggressive, highly monitored medical treatment. We reviewed data from three randomized controlled studies that published data comparing intracranial stenting vs. medical treatment for symptomatic severe-ICAD. Ethnic, demographic, clinical, and procedural differences were observed among the data from these trials that might influence their results. Future research should aim at establishing refined selection criteria that can identify high-risk ICAD patients who may benefit from intracranial stenting.